RETRACTED: Inhibitor 9 Combined With Androgen Deprivation Therapy or Chemotherapy Delays the Malignant Behavior of Castration-Resistant Prostate Cancer Through K-Ras/PLCε/PKCε Signaling Pathway - Liu, Jiayu; Zheng, Yongbo; Gao, Yingying; Quan, Zhen; Qiao, Bo; Li, Luo; Li, Ting; Duan, Limei; Yang, Jinxiao; Luo, Chunli; Wu, Xiaohou (Frontiers in Oncology, 2020)
Castration Resistant Prostate Cancer (CRPC) is a progressed stage of prostate cancer, which requires better understanding of the mechanisms and remains an unmet clinical need. As a common oncogene, K-Ras is associated with malignant behavior in different types of tumors but its role in CRPC is unknown. The present study aims to find the mechanism of K-Ras in CRPC and whether it can be used as a crucial molecule for the treatment of CRPC. For this purpose, tissue samples from primary prostate cancer (PPC) and CRPC patients were analyzed by immunohistochemistry and the data showed that K-Ras was elevated in CRPC. More importantly, higher K-Ras expression was related to a shorter recurrence‑free survival time in patients with CRPC. In addition, K-Ras promoted the invasion, migration and drug resistance of CRPC cells by activation of PLCε/ PKCε signaling pathway. Meanwhile, the inhibitor of K-RasG12C mutants was able to inhibit malignant behavior of CRPC cells in vitro and in vivo. Inhibitors of K-RasG12C mutants have entered clinical trial. Taken together, the study shows that K-Ras may activate PKCε through PLCε, resulting in the alterations of malignant behavior of CRPC. Inhibitor 9, an inhibitor of the K-RasG12C mutant, has a strong anti-tumor effect in CRPC, which potentially suggests that inhibitors of this nature may serve as a promising treatment for CRPC.